An integrated approach to model redispatch and to assess potential benefits from market splitting in Germany - Katrin Trepper; Michael Bucksteeg; Christoph Weber (University of Duisburg-Essen, Chair for Management Science and Energy Economics, 2014)
Future congestion management is one of the major market design issues in the European electricity market. In the light of the sharp increase in redispatch measures seen within the last years, the importance of an efficient management of network congestion increases particularly in Germany. Against this background, we develop an integrated approach to model (re)dispatch for Germany in detail while considering interactions with neighbouring countries. Compared to 2011, our findings indicate a much more critical network situation in Germany for 2015. We identify increased RES production, resulting imports and exports, delays in grid extension and the impacts of the nuclear phase-out (leading to an amplified north-south congestion problem) as main drivers for the nearly doubling of redispatch volumes in 2015. We show that market splitting can potentially contribute to a secure grid operation and leads to a significant reduction of redispatch volumes (59%) according our model calculations. We state that market splitting can of course not be the `one and only solution' but an interim approach to manage upcoming congestion in Germany in times when grid expansion has not yet been completed and that the implementation of market splitting can also serve as an alternative to grid extension within less congested areas.
Keywords: Q40; Q47; Q49; 330; redispatch; congestion management; market design; market splitting